EFFECT OF HYPNO-PRESSURE ON ANXIETY IN PATIENTS WITH CARDIOVASCULAR DISORDER - Dwi Antara Nugraha; Sri Endang Pujiastuti; Budi Widiyanto; Choiroel Anwar (Belitung Raya Foundation, Indonesia, 2018)
Objective: This study aimed to determine the effectiveness of the combination of hypnotherapy and acupressure (hypno-pressure) on anxiety levels in patients with cardiovascular disorders. Methods: A quasi-experimental research with pretest-posttest with control group design was used. Fifty-six respondents were selected using purposive sampling in this study, which 28 respondents were randomly assigned in the experiment and control group. The Spielberger State-Trait Anxiety Inventory (STAI) Form Y was used to measure anxiety. Paired t-test and Independent t-test were used for data analysis. Results: There was a significant effect of hypno-pressure on the decrease of anxiety levels in patients with cardiovascular disorder with p-value 0.000 (<0.05), t = 7.217, and effect size of 1.96. Conclusion: Hypno-pressure could reduce anxiety levels in patients with cardiovascular disorder.